Gênes et les réseaux du commerce du sucre à la fin du Moyen Âge - Mohamed Ouerfelli (Les Cahiers de Framespa)
This study investigates the role of the Genoa businessmen in the sugar trade in the Mediterranean in the late Middle Ages. It also addresses the fact that, if these businessmen demonstrated a progressive and continuous disinterest in this lucrative trade in the East, namely in the Kingdom of Cyprus, they, however, were more dynamic in Sicily and especially in the Kingdom of Granada. In this region, they firmly implanted and monopolized the exportation of sugar and dried fruit. Thus, they shipped products in their own merchant fleet to the North Sea. This success granted Genoa the chance of having a very early investment in the new sugar factories of the Atlantic Islands.